Characterisation of cellulolytic activity and bioconversion of palm kernel cake by lactic acid bacteria - Wan, Suet Ying (2015)
Cellulolytic enzyme is becoming more important due to its application in agro-wastes, which appear to be a potential substitution for production of bioenergy and biofuel. Lactic acid bacteria (LAB) isolated from Malaysian fermented food (Lactobacillus plantarum RG14, RG11, RI11, RS5, TL1, I-UL4 and B4) were characterised for their cellulolytic activities (CMCase, FPase, β-glucosidase, xylanase and mannanase assays) under different pH conditions (pH 5, 6.5 and 8). Two quantification methods (Bradford and modified Lowry methods) of protein concentration were conducted for the determination of specific celluloytic activity. Specific cellulolytic activities were 45 to 52 times higher when the protein concentration of cell-free supernatant was determined by Bradford method as compared to modified Lowry method. L. plantarum RG14, RG11 and RI11 were observed with higher scoring in overall cellulolytic activity and hence they were selected for biotransformation of palm kernel cake (PKC) via solid state fermentation (SSF) for 14 days with 2-day sampling intervals. The PKC extract was collected from fermented PKC to determine the cellulolytic activities and LAB population. The highest LAB cell population was observed at day 2 PKC extract treated by L. plantarum RG14 and RG11 with 8.15 log CFU/mL and 8.11 log CFU/mL, respectively. As for L. plantarum RI11, the highest cell population was noted at day 4 with 8.13 log CFU/mL. The cell population of LAB was maintained throughout the SSF. The solubilised protein concentration of PKC extract determined using modified Lowry method increased according to the SSF period, whereas a decrement in solubilised protein concentration was observed when Bradford method was employed. This might due to lower sensitivity and linearity in Bradford method in comparison to modified Lowry method. Hence, the specific cellulolytic activity of PKC extract was determined using modified Lowry method under pH condition at 5. The CMCase activity was enhanced at day 6, followed by a drastic decline. The β-glucosidase activity was increased during the SSF with the highest activity observed at day 12 when PKC was treated by L. plantarum RG14 and day 14 by L. plantarum RG11 and RI11respectively. A significant enhancement in specific mannanase activity was exhibited at the 8th day of incubation. Unfortunately, no FPase activity was detected throughout the fermentation period. Interestingly, the specific cellulolytic activity obtained through submerged fermentation in MRS broth was higher as compared to PKC extract obtained through SSF. This was due to MRS broth provided sufficient moisture and nutrient to support the growth and enzyme production in LAB isolates. In conclusion, the LAB isolates were able to produce versatile cellulolytic enzymes to degrade various forms of polysaccharides and PKC. Thus, the cellulolytic enzymes of LAB possessed vast potential for biotransformation of biomass.